2019
DOI: 10.1088/1742-6596/1410/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

Structure of V-defects in a-GaN films grown on r-sapphire substrate

Abstract: The a-GaN films were successfully grown on the r-sapphire substrate by MOCVD method. The structure of V-defects was investigated by AFM and SEM. The dependence of V-defects density on growth temperature of a-GaN film at a constant hydrogen flow through a TEG source was studied. The influence of V/III ratio on V-defects structure was investigated. Methods of V-defects density minimisation were purposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Small pits were then formed on the TD core. When the growth temperature of InGaN is lowered, the growth rate of the (10)(11) plane is lower than that of the (0001) plane, causing the formation of V-defects along the six sloping (10-11) sidewalls. On one hand, increasing the temperature enhances the surface Ga and In atomic mobility, reducing the number of pit cores.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Small pits were then formed on the TD core. When the growth temperature of InGaN is lowered, the growth rate of the (10)(11) plane is lower than that of the (0001) plane, causing the formation of V-defects along the six sloping (10-11) sidewalls. On one hand, increasing the temperature enhances the surface Ga and In atomic mobility, reducing the number of pit cores.…”
Section: Resultsmentioning
confidence: 99%
“…We further tested the surface topography of the three samples using AFM over a larger area, and the results are shown in figure 5. It indicates that surface morphology deteriorates and the defect densities increases when the growth temperature decreases from 810 °C to 785 °C, which is attributed to the different growth rate between (10)(11) and (0001). It is reported that the different growth rate on (10-11) will decrease when growth temperature decreases, and the surface migration of Ga and In atoms will also decrease Therefore, increasing the temperature can effectively reduce the defect density of V-defects to a certain extent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation